RAY LAURENCE, ROMAN ARCHAEOLOGY FOR HISTORIANS, ROUTLEDGE PUBLISHING HOUSE - Cosmin Coatu (Journal of Ancient History and Archaeology, 2015)
Ray Laurence, Roman Archaeology for Historians, Routledge Publishing House